A Content Analysis of Listening Activities in An Indonesian EFL English Textbook: Alignment with The Authenticity - Febriani, Karisma; Purwaningsih, Sundari; Hakim, Lystiana Nurhayat (Universitas Pahlawan Tuanku Tambusai, 2026)
This study investigates the types of listening activities and the extent to which they reflect authenticity in the Indonesian EFL textbook Bahasa Inggris untuk SMA/SMK/MAK Kelas 10 A published by Intan Pariwara. Through content analysis, the study identifies the distribution of listening activity types and examines the level of authenticity in both tasks and texts. The findings reveal that selective listening is the most dominant type, while extensive listening is absent. In terms of authenticity, most tasks and texts are semi-authentic, with limited fully authentic materials. These results indicate that the textbook emphasizes controlled and form-focused listening practice, offering limited opportunities for learners to engage with real-life spoken English. The study highlights the need for more diverse and authentic listening inputs to better support students’ communicative competence in EFL contexts.